2012
DOI: 10.5001/omj.2012.03
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Mycobacterium Tuberculosis Induced Reactive Oxygen Species andTumor Necrosis Factor-Alpha Activity in Human Monocytes of Systemic LupusErythematosus Patients by Reduced Glutathione

Abstract: Data shows that SLE patients are more susceptible to developing Mycobacterium tuberculosis, as ROS and TNF-α in SLE patients could activate the replication of mycobacterial Ag85B (30 kDa) after bacilli infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…This produces ∙O 2 which dismutate into hydrogen peroxide (H 2 O 2 ) and thus generate ∙OH radicals which are toxic to MTB [ 20 ]. Following inhalation of MTB, alveolar macrophages engulf the bacilli and initiate their killing using a number of mechanisms including the generation of ROI and RNI [ 21 , 22 ].…”
Section: Role Of Reactive Oxygen Specious (Ros) In Pathogenesis Of Tbmentioning
confidence: 99%
See 1 more Smart Citation
“…This produces ∙O 2 which dismutate into hydrogen peroxide (H 2 O 2 ) and thus generate ∙OH radicals which are toxic to MTB [ 20 ]. Following inhalation of MTB, alveolar macrophages engulf the bacilli and initiate their killing using a number of mechanisms including the generation of ROI and RNI [ 21 , 22 ].…”
Section: Role Of Reactive Oxygen Specious (Ros) In Pathogenesis Of Tbmentioning
confidence: 99%
“…Thus, NADPH oxidase has an important role in host defense against MTB and any patients with a loss of function mutation in genes encoding components of this enzyme complex could be deficient in killing bacilli. Indeed, mutations in the CYBB gene encoding the gp91 (phox) subunit of the phagocyte NADPH oxidase is associated with MTB [ 21 ]. In addition, a hemizygous splice mutation in intron 5 of CYBB was linked to the concomitant occurrence of chronic granulomatous disease (CGD) with MTB [ 24 ].…”
Section: Role Of Reactive Oxygen Specious (Ros) In Pathogenesis Of Tbmentioning
confidence: 99%
“…When the body is activated during infection or tissue damage, it can transmit signals via ligands and receptors back to cells, causing subsequent inflammatory cascade reactions [ 39 ]. TNF- α can not only induce a massive release of a variety of inflammatory factors and stimulate the development of inflammation [ 40 ] but also directly consume the antioxidant substance glutathione in the body [ 41 ] and stimulate neutrophils and endothelial cells to release oxygen free radicals and other free radicals [ 42 ]. MAPK14 (p38) and MAPK8 (JNK) can receive and prolong the path and duration of TNF signal transduction and jointly affect the level of systemic inflammation response, the area of tissue damage, and the degree of organ function impairment by activating NF- κ B [ 43 ].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, Iliaz et al ( 37 ) indicated that neutrophil/lymphocyte ratio could be used as a reference in the differential diagnosis of tuberculosis. Furthermore, previous investigations have suggested that suppression of M. tuberculosis growth can upregulate TNF-α, which increases the levels of human monocytes in patients with pulmonary tuberculosis ( 38 , 39 ). These reports suggest that inhibition of inflammatory cells may be a potential target for the treatment of pulmonary tuberculosis.…”
Section: Discussionmentioning
confidence: 99%